Association of persistent and transient worsening renal function with mortality risk, readmissions risk, length of stay, and costs in patients hospitalized with acute heart failure - Palmer JB; Friedman HS; Waltman Johnson K; Navaratnam P; Gottlieb SS (Dove Medical Press, 2015)
Jacqueline B Palmer,1 Howard S Friedman,2 Katherine Waltman Johnson,1 Prakash Navaratnam,2 Stephen S Gottlieb3 1Novartis Pharmaceuticals Corporation, East Hanover, NJ, USA; 2DataMed Solutions, LLC, New York, NY, USA; 3Department of Medicine, University of Maryland School of Medicine, Baltimore, MD, USA Background: Data comparing effects of transient worsening renal function (WRFt) and persistent WRF (WRFp) on outcomes in patients hospitalized with acute heart failure (AHF) are lacking. We determined the characteristics of hospitalized AHF patients who experienced no worsening renal function (non-WRF), WRFt, or WRFp, and the relationship between cohorts and AHF-related outcomes. Methods and results: A patient’s first AHF hospitalization (index) was identified in the Cerner Health Facts® database (January 2008-March 2011). Patients had WRF if serum creatinine (SCr) was ≥0.3 mg/dL and increased ≥25% from baseline, and they were designated as WRFp if present at discharge or WRFt if not present at discharge. A total of 55,436 patients were selected (non-WRF =77%, WRFp =10%, WRFt =13%). WRFp had greater comorbidity burden than WRFt. At index hospitalization, WRFp patients had the highest mortality, whereas WRFt patients had the longest length of stay (LOS) and highest costs. These trends were observed at 30, 180, and 365 days postdischarge and confirmed by multivariable analyses. WRF patients had more AHF-related readmissions than non-WRF patients. In sensitivity analyses of the patient subset with live index hospitalization discharges, postdischarge LOS and costs were highest in WRFt patients, whereas mortality associated with a HF hospitalization was significantly higher for WRF patients vs non-WRF patients, with no difference between WRFp and WRFt. Conclusion: In patients hospitalized for AHF, WRFp was associated with the highest mortality, whereas WRFt was associated with the highest LOS and costs. WRF patients had higher readmissions than non-WRF patients. Transient increases in SCr appear to be associated with detrimental outcomes, especially longer LOS and higher costs. Keywords: renal function, acute heart failure, mortality rate, health outcomes, serum creatinine, cost